Interests and preferences towards technology-based cardiac rehabilitation in men and women with coronary artery disease. (2nd July 2022) - Munoz Gomez, E; Orihuela, L; Deka, P; Klompstra, L; Pathak, D; Sempere-Rubio, N; Sentandreu-Mano, T; Mont, J; Moreno-Segura, N; Cruz, M; Westas, M; Marques-Sule, E
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Several studies have demonstrated the effectiveness of telemedicine programmes in patients with coronary artery disease (CAD). However, the development of these programmes is driven from a technical point of view and does not usually take into account the needs and expectations of patients. Thus, we found a need to study the interests and preferences towards technology-based cardiac rehabilitation (CR) in patients with CAD. Purpose: The aim of this study was to compare the interests and preferences towards technology-based CR in men and women with CAD. Method: A cross-sectional study was conducted. A total of 70 subjects with CAD (84.28% male) were included. Participants' interests and preferences were measured using the Technology Usage Questionnaire, which includes items on digital health and technology usage. Results: On the one hand, men showed a greater interest in receiving CR counselling via mobile phone (p=0.022), would sign up for a free technology-based CR programme (p=0.034) and would like to receive less than 1-2 messages a week (p=0.010). On the other hand, women showed greater interest in receiving information about the different components included in the CR programme (receiving healthy meal/recipe ideas (p=0.002), reminders to take medication (p=0.039) and showed greater interest in meeting other people with heart disease (p=0.034). No differences were found by gender in type of communication that participants would like to receive through their mobile phone (p=0.154) or through the Internet (p=0.648), interest in receiving treatment through the Internet (p=0.454), interest in receiving an exercise-based CR program using virtual reality (p=0.810), nor usefulness of a virtual CR session (p=0.801). Conclusions: In subjects with CAD, gender appears to be a determinant of interest. Men showed a greater interest in receiving CR counselling via mobile phone, would sign up for a technology-based CR programme and would like to receive fewer notifications. Women were more interested in receiving information about different components of the CR programme.